Gag Protein Epitopes Recognized by ELA-A-Restricted Cytotoxic T Lymphocytes from Horses with Long-Term Equine Infectious Anemia Virus Infection - Zhang, Wei (American Society for Microbiology, 1998)
Most equine infectious anemia virus (EIAV)-infected horses have acute clinical disease, but they eventually control the disease and become lifelong carriers. Cytotoxic T lymphocytes (CTL) are considered an important immune component in the control of infections with lentiviruses including EIAV, but definitive evidence for CTL in the control of disease in carrier horses is lacking. By using retroviral vector-transduced target cells expressing different Gag proteins and overlapping synthetic peptides of 16 to 25 amino acids, peptides containing at least 12 Gag CTL epitopes recognized by virus-stimulated PBMC from six long-term EIAV-infected horses were identified. All identified peptides were located within Gag matrix (p15) and capsid (p26) proteins, as no killing of target cells expressing p11 and p9 occurred. Each of the six horses had CTL recognizing at least one Gag epitope, while CTL from one horse recognized at least eight different Gag epitopes. None of the identified peptides were recognized by CTL from all six horses. Two nonamer peptide epitopes were defined from Gag p26; one (18a) was likely restricted by class I equine leukocyte alloantigen A5.1 (ELA-A5.1) molecules, and the other (28b-1) was likely restricted by ELA-A9 molecules. Sensitization of equine kidney target cells for CTLm killing required 10 nM peptide 18a and 1 nM 28b-1. The results demonstrated that diverse CTL responses against Gag epitopes were generated in long-term EIAV-infected horses and indicated that ELA-A class I molecules were responsible for the diversity of CTL epitopes recognized. This information indicates that multiple epitopes or whole proteins will be needed to induce CTL in horses with different ELA-A alleles in order to evaluate their role in controlling EIAV.